Reconstruction of Craniectomy for Microvascular Decompression with Autologous Particulate Bone - Liu, Weichao; Yuan, Ye; Xiong, Nanxiang; Wang, Qiangping; Zhang, Fangcheng; Zhao, Hongyang; Xu, Hao; Nayaz, Alading; Hendrik, Pool; Sean, Dickinson James (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Objective Cranioplasty after microvascular decompression (MVD) is important for preventing postoperative complications such as headache. Autologous particulate bone is a common material for cranioplasty. The purpose of this study was to evaluate the effect of using autologous particulate bone to reconstruct the cranial defect produced by MVD.Patients and Methods Data were collected from January 2013 to December 2016 from 243 patients who underwent suboccipital retrosigmoidal craniectomy for MVD. The patients were then further divided into two groups: in the first group (from January 2013–October 2015), a cranioplasty was performed using a combination of bone dust (taken from a power drill) and particulate bone (harvested with a rongeur); in the second group (from November 2015–December 2016), the cranial defect was reconstructed using particulate bone alone. Healing of the cranial defect was observed during the follow-up.Results Early postoperative computed tomography (CT), performed during the hospital stay, revealed that the filling of the cranial defects of the first group was better than that of the second group. In addition, surgical-site infections (SSIs) occurred in 13 patients in the first group (9.92%) versus 2 patients in the second group (1.79%). The SSI rate of the first group was significantly higher than that of the second group (p < 0.05). Long-term follow-up CT demonstrated that the average reconstruction rate ((volume of the reconstruction area)/(volume of the cranial defect) × 100%) was 47.88% for the first group and 43.94% for the second group (p > 0.05).Conclusion The use of autologous particulate bone to reconstruct cranial defects after MVD has a good effect and is thus a useful and valuable technique. Bone dust may result in a higher incidence of SSI.
Keywords: craniectomy; microvascular decompression; skull reconstruction; surgical-site infection